Del sonido al homenaje: investigación creación de tres obras contemporáneas en diferentes formatos (2020)
This research describes the creative process, technical resources and aesthetic reflections around the composition of three contemporary works for different media and formats (i- solo instrument, ii- electroacoustic iii- and mixed). The concept that motivates the referential axis of all the pieces is that of homage. Each chapter focuses on describing the way in which the honored subjects are represented symbolically and referentially, thus showing the relationship with the instrumental media and sounds chosen for each piece in this portfolio.--Taken from the Degree Document Format.